Intercropping optimizes soil temperature and increases crop water productivity and radiation use efficiency of rainfed potato - Nyawade, S.; Karanja, N.; Gachene, C.K.K.; Gitari, H.I.; Schulte-Geldermann, Elmar; Parker, M. (Springer, 2019)
Integrating crop species with different photosynthetic pathways has great potential to increase efficiency in the use of scarce resources. In order to tap the resource complementarity emanating from this mix, this study intercropped potato (Solanum tuberosum L.) with lima bean (Phaseolus lunatas L.) and dolichos (Lablab purpureous L.), and related soil temperature with radiation use efficiency and crop water productivity of rainfed potato in the upper midland (1552 m above sea level (masl), lower-highland (1854 masl) and upper-highland (2553 masl)) agro-ecological zones of Kenya. Leaf area index (LAI), light interception, soil temperature and soil water contents (SWC) were quantified at different stages of potato growth and related with the radiation use efficiency (RUE) and crop water productivity (CWP) of potato. Intercropping increased crop LAI by 26–57% relative to sole potato stands and significantly lowered the soil temperatures in the 0–30 cm depth by up to 7.3 °C. This caused an increase in SWC by up to 38%, thus increasing RUE by 56–78% and CWP by 45–67%. Intercropping potato with legumes is coupled with optimum root-zone soil temperature and soil water content, thus potentially exerting additive relations in radiation interception and subsequent conversion into crop biomass.